Examining The Determinants Of Inflation, GCG and NPF in The Context of Increasing Profitability - Alfiana Alfiana; Elsya Meida Arif; Kampono Imam Yulianto; Ngurah Pandji Mertha Agung Durya; Lili Syafitri (International Journal of Economics Development Research (IJEDR), 2023)
Competition of business is so tight, however the development of Islamic Commercial Banks the longer shows that the positive trend can not be separated from the role of Good Corporate Governance who are important in providing regulates the company's own operational system. This study aims to analyze and examine the factors that influence the Return on Asset at Islamic Commercial Banks in 2018-2022 period. These factors include inflation, GCG and NPF. The method of research is using the quantitative and regression analysis, the sample is Islamic Commercial Banks which are consistently publish quarterly financial reports period 2018-2022 with a total of 12 companies. Researcher collected the data by saturation sampling method, and it is analyzed with EViews 10. Analysis was carried out by several tests such as classic assumption test, feasibility analysis model, panel regression analysis and coefficient of determination test. Based on research, ROA of Islamic banks is influenced by GCG and NPF, while the inflation does not have an influence on Islamic Commercial Banks period 2018-2022. Thus, every bank must show good financial performance in order to obtain higher profitability. The benefit of research in banking is to be able to assess a company's ability to earn profits from the assets used.